Reliable and specific detection and identification of Brenneria goodwinii, the causal agent of oak and oriental beech decline - Araeinejhad, Mohammad-Hossein; Charkhabi, Nargues Falahi; Brady, Carrie; Rahimian, Heshmat (Frontiers in Forests and Global Change, 2024)
Chestnut-leaved oak (Quercus castaneifolia) and oriental beech (Fagus orientalis) are among the major tree species in the Hyrcanian forests. Brenneria goodwinii was identified as the causal agent of necrotic lesions and stem bleeding on affected oak trees in different countries. Oak and oriental beech trees with bleeding symptoms were observed in a few forest sites in northern Iran. The objectives of the present study were to identify and characterize the causal agents of bark canker in oak and oriental beech trees and develop a primer set for specific detection, using polymerase chain reaction (PCR), of Brenneria goodwinii strains. A total of 31 and 20 samples from oak and oriental beech trees, respectively, with stem bleeding and bark canker symptoms were collected from Golestan and Mazandaran forests in northern Iran in 2020–2021. Bacterial strains displaying a green metallic sheen on EMB-agar medium were isolated from symptomatic oak (105 strains) and oriental beech samples (32 strains), while 31 and 20 strains were also isolated from healthy oak and oriental beech, respectively. Pathogenicity tests indicated that 51 and 25 strains isolated from oak and oriental beech, respectively were able to induce a necrotic area on oak acorns 15 days following inoculation. Moreover, four and two representative strains inoculated on oak and oriental beech twigs, respectively induced necrosis on all inoculated green twigs 1 month after inoculation. The sequences of the 16S rRNA and gyrB genes of representative strains isolated from and proved pathogenic on oak and oriental beech trees were 100% and over 99% similar to B. goodwinii LMG 26270T, respectively, which revealed the strains belong to B. goodwinii species. The primer pair BgF3/R2, which was designed to target the hrpN gene, was proven to be specific in the detection of B. goodwinii strains. The primer pair amplified a 618-bp DNA fragment from strains of B. goodwinii only and not from strains belonging to Rahnella, Gibbsiella, Lonsdalea, and the other Brenneria species among several other pathogenic bacteria tested. No fragment was amplified from DNA extracted from healthy trees or seedlings in PCR using this primer pair.